2013
DOI: 10.5539/ass.v9n17p163
|View full text |Cite
|
Sign up to set email alerts
|

Thai Migrant Workers in Agriculture Farms in New Zealand: A Short Case Study

Abstract: This paper's aim is to study the problems Thai migrant workers face in agricultural farming in New Zealand and to provide guidelines for solving these problems. This study used in-depth interviews conducted between the years 2007 and 2012, with accidental sampling, and the data were analyzed using a content analysis. The study found that the main motivation of Thai workers is to send remittance back home to pay off family debt. Many Thai workers came to work in New Zealand because their relatives motivated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Research has found migrant workers experience exploitation and exploitative labour conditions in certain industry sectors in New Zealand. These are agriculture (Caritas, 2016;Stringer, 2016;Promsaka Na Sakolnakorn et al, 2013;Tipples et al, 2012), horticulture and viticulture (Caritas, 2016;Stringer, 2016;Prochazkova, 2013;Anderson et al, 2012;Anderson and Naidu, 2010;Beer and Lewis, 2006), fisheries (Macfarlane, 2017;Stringer, 2016;Stringer et al, 2016;Simmons and Stringer, 2014), construction (Stringer, 2016;Searle, McLeod and Ellen-Eliza, 2015), hospitality (Caritas, 2016;Stringer, 2016;Searle, McLeod and Stichbury, 2015), and health care services (Lovelock and Martin, 2016;Peligman-Toclo, 2011;Walker, 2008;Manchester, 2005;O'Connor, 2005). This small body of research about migrant exploitation in certain New Zealand industry sectors consistently showed the same types of exploitation or poor labour conditions were occurring across sectors.…”
Section: Exploitation In New Zealandmentioning
confidence: 99%
“…Research has found migrant workers experience exploitation and exploitative labour conditions in certain industry sectors in New Zealand. These are agriculture (Caritas, 2016;Stringer, 2016;Promsaka Na Sakolnakorn et al, 2013;Tipples et al, 2012), horticulture and viticulture (Caritas, 2016;Stringer, 2016;Prochazkova, 2013;Anderson et al, 2012;Anderson and Naidu, 2010;Beer and Lewis, 2006), fisheries (Macfarlane, 2017;Stringer, 2016;Stringer et al, 2016;Simmons and Stringer, 2014), construction (Stringer, 2016;Searle, McLeod and Ellen-Eliza, 2015), hospitality (Caritas, 2016;Stringer, 2016;Searle, McLeod and Stichbury, 2015), and health care services (Lovelock and Martin, 2016;Peligman-Toclo, 2011;Walker, 2008;Manchester, 2005;O'Connor, 2005). This small body of research about migrant exploitation in certain New Zealand industry sectors consistently showed the same types of exploitation or poor labour conditions were occurring across sectors.…”
Section: Exploitation In New Zealandmentioning
confidence: 99%